STABILITAS STATIS KAPAL PURSE SEINE MUNCAR (Studi Kasus Pada Salah Satu Kapal Purse Seine di Muncar) - Budhi Hascaryo Iskandar; Rika Ike Rahayu (Buletin PSP, 2008)
This paper discusses on static stability of Muncar purse seiner. The purse seiner data was obtained from the previous research which discussed on its design and constructions. A case study method was applied in this research. The objective of the research is to determine stability static quality of Muncar purse seiner.Some analysis was applied in this research such as, ratio dimension analysis, hydrostatic analysis and static stability value of the ship. The result showed that, ratio dimension of the ship (L/B, L/D, B/D) followed general range of Indonesian purse seiner, its coeffisien of fineness were within a range of purse seiner in Indonsia as well. Based on static stability analysis with 7 (seven) operational conditions taken into account, showed that the ship had good stability and suitable for non-extrem waters operationed.